2021
DOI: 10.1002/jgh3.12540
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular management of portal steal syndrome due to portosystemic shunts after living donor liver transplantation

Abstract: Background and Aim: After liver transplant, pre-existent porto-systemic shunts (PSS) may persist, causing "portal steal," leading to graft dysfunction, hepatic encephalopathy (HE), and eventual rejection. In recipients of small-for-size transplant liver grafts, shunts may be created intraoperatively, facilitating diversion of portal flow to systemic circulation to avoid ill-effects of portal overperfusion. These iatrogenic shunts may also subsequently lead to portal steal. We aim to evaluate safety and efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Esophageal and gastric varices can lead to the formation of a gastrorenal or splenorenal shunt, which becomes interlinked with the systemic circulation. [ 18 ] The clinical significance of spontaneous portosystemic shunt formation is that on the one hand, the shunt can share part of the portal vein pressure, whereas on the other hand, gastric variceal bleeding after the formation of the shunt channel increases the risk of ectopic embolization during endoscopic embolization treatment, and the formation of spontaneous portosystemic shunts channel makes the treatment of gastric variceal bleeding very difficult. [ 19 ] A study of 700 patients with cirrhosis combined with portal hypertension demonstrated spontaneous portosystemic shunts in 16.86% of patients (gastrorenal shunt in 7.14% and splenorenal shunt in 8.43%).…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal and gastric varices can lead to the formation of a gastrorenal or splenorenal shunt, which becomes interlinked with the systemic circulation. [ 18 ] The clinical significance of spontaneous portosystemic shunt formation is that on the one hand, the shunt can share part of the portal vein pressure, whereas on the other hand, gastric variceal bleeding after the formation of the shunt channel increases the risk of ectopic embolization during endoscopic embolization treatment, and the formation of spontaneous portosystemic shunts channel makes the treatment of gastric variceal bleeding very difficult. [ 19 ] A study of 700 patients with cirrhosis combined with portal hypertension demonstrated spontaneous portosystemic shunts in 16.86% of patients (gastrorenal shunt in 7.14% and splenorenal shunt in 8.43%).…”
Section: Discussionmentioning
confidence: 99%